A successive pro-environmental behaviour framework. Issue 1 (25th February 2019) - Tavri, Purva
Abstract : This paper presents a successive pro-environmental behaviour framework based on four key models that develop a common argument that, in instances where communicating information is insufficient for triggering and maintaining changes in behaviour, other strategies are needed. These four models are the 'theory of planned behaviour' framework of Ajzen and Fishbein, a model of pro-environmental behaviour by Kollmuss and Agyeman, a conceptual model for recycling behaviour change by Valle et al. and Stern's value-belief-norm model. The resultant pro-environmental behaviour framework has been used as an analytical tool to inform the methodology, and for carrying out the empirical work to investigate re-use behaviour at the organisational level in the UK. The framework is developed by analysing broad areas of argument in relation to pro-environmental behaviour: how it is developed and how it can be maintained. This paper presents the combination of snowballing and an inductive approach as appropriate methods utilised, respectively, for the selection of studies and the development of the successive pro-environmental framework. The successive pro-environmental framework is called communication, engagement/action, behavioural maintenance and avoidance of the value action gap, or CEBA for short.